2017
DOI: 10.1016/j.aim.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Hausdorff dimension of univoque sets and Devil's staircase

Abstract: Abstract. We fix a positive integer M , and we consider expansions in arbitrary real bases q > 1 over the alphabet {0, 1, . . . , M }. We denote by U q the set of real numbers having a unique expansion. Completing many former investigations, we give a formula for the Hausdorff dimension D(q) of U q for each q ∈ (1, ∞). Furthermore, we prove that the dimension function D : (1, ∞) → [0, 1] is continuous, and has a bounded variation. Moreover, it has a Devil's staircase behavior in (q ′ , ∞), where. During the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
111
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 29 publications
(48 reference statements)
0
111
0
Order By: Relevance
“…For more information on these sets we refer the reader to [7,5,9,6,11,12] and the references therein. Before continuing with our discussion of the sets U α,M and U α,M we make a brief remark.…”
Section: Preliminariesmentioning
confidence: 99%
“…For more information on these sets we refer the reader to [7,5,9,6,11,12] and the references therein. Before continuing with our discussion of the sets U α,M and U α,M we make a brief remark.…”
Section: Preliminariesmentioning
confidence: 99%
“…Recently, de Vries and Komornik investigated their topological properties in [8]. Komornik et al considered their Hausdorff dimension in [19], and showed that the dimension function D : q → dim H U q behaves like a Devil's staircase on (1, M +1]. For more information on the univoque set U q we refer to the survey paper [15] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that U is a Lebesgue null set of full Hausdorff dimension (cf. [6,12,19]). Moreover, the smallest element of U is the Komornik-Loreti constant (cf.…”
Section: Introductionmentioning
confidence: 99%
“…[11]). Erdős and Joó proved that U has Lebesgue measure zero [14], Daróczy and Kátai [10] later showed that U has full Hausdorff dimension (see also, [18,Theorem 1.6]). Recently, de Vries et al [12,Theorem 1.2] proved that its closure U is a Cantor set, i.e., a nonempty compact set with empty interior and no isolated points.…”
mentioning
confidence: 99%
“…In [18] the authors proved that the entropy function H is a Devil's staircase (see e.g., Figure 1), i.e., H satisfies the following:…”
mentioning
confidence: 99%